Upaya Guru BK dalam Meningkatkan Perilaku Moral Siswa di SMP PAB 2 Helvetia - Dewi Rizka Maulida Rambe; Mahidin Mahidin; Akmal Walad Ahkas (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to describe and determine the results of the application of efforts made by the Counseling Guidance teacher and explain the inhibiting and supporting factors in improving the moral behavior of students at PAB 2 Helvetia Junior High School. The type of research used is descriptive qualitative research. The research subjects consisted of Counseling Guidance teachers, Subject Teachers and Principals. The data collection methods used are observation, interviews and documentation. The data obtained were analyzed using descriptive qualitative with the stages of reducing data, displaying data and drawing conclusions. The results showed that the efforts made by the Counseling Guidance teacher included the application of sanctions and the application of warning letters for those who committed violations. There are several inhibiting factors from the efforts made by the Counseling Guidance teacher, namely the existence of students who fight when given a warning, lack of religious education and lack of guidance from parents and the environment of the students. Supporting factors are facilities and infrastructure from the school and awareness to be better than the students themselves. From the efforts, inhibiting and supporting factors in improving the moral behavior of students at SMP PAB 2 Helvetia, it was found that there was an increase in the moral behavior of students. This can be seen from the number of cases and the quantity of students who have slow problems.